Kajian Land Value Capture Kota Semarang - Aprih Santoso; Indraya Indraya; Emaya Kurniawati (Jurnal Riptek, 2022)
The purpose of analyzing the application of the Land Value Capture (LVC) approach in infrastructure development. This study uses a qualitative methodology to gain an understanding of the concept of value capture and institutional design approaches in certain contexts. The approach method that will be used to carry out this work is in the form of: inventory, analysis and discussion which can further be in the form of: Desk Study (literature study): best practice, related literature and Primary Survey: direct observation in the field. The results of the study are the following factors: the determinants of the success of the implementation of the LVC policy in Semarang City are very likely to make LVC an alternative funding for infrastructure, however, in order to achieve the successful implementation of LVC, the Semarang City government must be able to overcome various challenges.